Actual bovine tuberculosis situation in the Republic of Dagestan - M. O. Baratov; P. S. Huseynova (Ветеринария сегодня)
Lack of statistical data and inconsistences in science and practice make it impossible to give at least approximate tuberculosis prevalence rates in the Republic of Dagestan. Every year the number of tuberculin reacting animals is increasing. For example out of 2,944 tested heifers of breeding age in 2014–2019, up to 30% of animals had positive reactions in tests. During this period out of 1,166 emergency slaughtered animals, tuberculosis was confirmed in 326 animals (28%). Bacteriological tests revealed 291 mycobacterium cultures, 107 out of them were Mycobacterium bovis, the other 184 cultures were identified as atypical ones. Based on the species differentiation of 58 cultures, 22 Group II cultures (according to Runyon classification) were isolated; 18 out of them belonged to Mycobacterium gordonae, 2 to Mycobacterium flavescens, and species of two cultures could not be identified. Four cultures of Group III were species of Mycobacterium intracellulare. Out of 32 cultures of Group IV, two belonged to Mycobacterium smegmatis, seven to Mycobacterium fortuitum and one to Mycobacterium phlei, 22 cultures were not identified. To elucidate the role of milk in tuberculosis epidemiology 82 samples of milk from reactors from two farms were tested. In the farm, where reactors were awaiting their removal for a long time, mycobacteria were detected in 20% of milk samples, whereas in the recently infected farm the detection rate was 4%, which suggests that long awaiting periods present high risks. Microscopic, conventional phenotypic and targeted biochemical tests indicate that pseudo-allergic reactions, revealed by tests, result from the atypical mycobacteria of the mentioned groups and species, which present in the animal organism, and seem to be responsible for the tuberculin sensibilization. Timely and comprehensive diagnostic and animal health measures will improve the situation.